Maximum Reproductive Lifespan Correlates with CD33rSIGLEC Gene Number: Implications for NADPH Oxidase-derived Reactive Oxygen Species in Aging - Khan, Naazneen (FASEB J, 2019)
Humans and orcas are among the very rare species that have a prolonged post-reproductive lifespan (PRLS), during which the aging process continues. Reactive oxygen species (ROS) derived from mitochondria and from the NADPH-oxidase (NOX) enzymes of innate immune cells are known to contribute to aging, with the former thought to be dominant. CD33-related-Siglecs are immune receptors that recognize self-associated-molecular-patterns and modulate NOX-derived-ROS. We herewith demonstrate a strong correlation of lifespan with CD33rSIGLEC gene number in 26 species, independent of body weight or phylogeny. The correlation is stronger when considering total CD33rSIGLEC gene number rather than those encoding inhibitory and activating subsets, suggesting that lifetime balancing of ROS is important. Combining independent lines of evidence including the short half-life and spontaneous activation of neutrophils, we calculate that even without inter-current inflammation, a major source of lifetime ROS exposure may actually be neutrophil NOX-derived. However, genomes of human supercentenarians (>110yrs) do not harbor a significantly higher number of functional CD33rSIGLEC genes. Instead, life-span correlation with CD33rSIGLEC gene number was markedly strengthened by excluding the post-reproductive lifespan of humans and orcas (R(2)=0.83; p<0.0001). Thus, CD33rSIGLEC modulation of ROS likely contributes to maximum reproductive lifespan, but other unknown mechanisms could be important to PRLS.